Circular shifts: insights into kazakhstan's circular business ecosystem - Nurlyaiym Zhaksybayeva; Aisara. Serikkyzy; Asem. Baktymbet; Shumaila Yousafzai (Cogent Business & Management, 2024)
This study explores the role of circular entrepreneurship in advancing sustainable development within Kazakhstan, an emerging market traditionally reliant on resource-intensive economic practices. The circular economy, with principles of reduce, reuse, recycle, and recover, offers a transformative alternative to the linear `take-make-waste' model by promoting resource efficiency and waste minimization. Circular entrepreneurs are pivotal in this transition, particularly in emerging economies, where they address environmental challenges while creating new market opportunities. Despite its potential, circular entrepreneurship in Kazakhstan faces significant challenges, particularly for small and medium-sized enterprises (SMEs). These challenges include limited policy support, inadequate infrastructure, and a lack of public awareness about sustainable practices. This study employs a qualitative approach, including interviews and netnography, to investigate the motivations, operational dynamics, and challenges faced by SMEs in Kazakhstan that have integrated circular economy principles into their business models. The findings reveal that while Kazakhstan has made strides in promoting sustainable development through initiatives like the `Green Economy' Plan, there are still substantial gaps in policy and institutional support for circular entrepreneurship. The study underscores the need for targeted strategies to enhance public awareness, provide financial incentives, strengthen regulatory frameworks, and foster collaboration among stakeholders. This research contributes to the broader understanding of circular entrepreneurship in emerging markets, offering policy recommendations that aim to support the growth of circular businesses and accelerate Kazakhstan's transition to a circular economy. By highlighting the unique challenges and opportunities in this context, the study provides valuable insights for policymakers, entrepreneurs, and other stakeholders committed to sustainable development.
Keywords: 650; Circular economy; circular entrepreneurship; developing countries; emerging economies; Kazakhstan; Central Asia